Cuban Exceptionalism Revisited - Bert Hoffmann; Laurence Whitehead (German Institute of Global and Area Studies (GIGA), 2006)
The end of Cuban exceptionalism has been much announced since 1989, but a decade and a half later state socialism on the island is still enduring. Transition studies have been criticized for focusing on success stories. Exploring the deviant case of Cuba's 'non-transition' from a comparative social science perspective can shed light on the peculiarities of this case and, more importantly, test the general assumptions underlying post-1989 expectations of regime change in Cuba. Theories of path dependence and cumulative causation are particularly helpful when attempting to link Cuban current political exceptionalism with a more long-term historic perspective. Moreover, they suggest that interpretations of Cuba as simply a 'belated' case of 'third wave' democratization may prove erroneous, even when the health of Fidel Castro finally falters. – – Nach 1989 ist das Ende des kubanischen 'Sonderfalls' oft beschworen worden. Doch mehr als anderthalb Jahrzehnte nach dem Ende des Kalten Krieges behauptet sich der kubanische Staatssozialismus noch immer. Wo die Transitionsforschung für ihre Konzentration auf Erfolgsfälle kritisiert worden ist, kann aus komparativer Perspektive die Analyse der kubanischen 'Nicht-Transition' nicht nur den Fall selbst erhellen, sondern - und wichtiger noch - jene Annahmen untersuchen, die den Erwartungen eines Systemwechsels in Kuba nach 1989 zu Grunde lagen. Theorieansätze zu Pfadabhängigkeit und sich selbst verstärkender Ursachenketten ('cumulative causation') können Kubas gegenwärtigen politischen Exzeptionalismus im Rahmen einer längerfristigen historischen Perspektive analysieren. Zudem legen sie nahe, dass auch im Falle des Todes von Fidel Castro Sichtweisen wenig adäquat sein werden, die Kuba lediglich als 'Nachzügler' der 'dritten Demokratisierungswelle' verstehen interpretieren.
Keywords: 300; Cuba; comparative politics; exceptionalism; socialism; transition